Optimasi Nilai Perusahaan Property dan Real Estate: Analisis Good Corporate Governance (GCG), Profitabilitas, dan Struktur Modal - Dita Sobiroh; Ana Kadarningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This study aims to analyze the impact of good corporate governance, profitability, and capital structure on company value in property and real estate subsector companies that are verified on the Indonesia Stock Exchange (BEI). This population study uses a purposive sampling method through real estate and property subsector companies verified on the Indonesia Stock Exchange from 2018-2022. Through predetermined conditions, 43 companies were taken as samples, with a total of 215 data analyzed. This study uses the method of descriptive statistical analysis, multiple linear regression tests, classical assumptions and hypotheses. The results of the study partially observed that good corporate governance as proxied by the independent board of commissioners had a significant negative impact on company value, profitability as proxied by return on assets had a significant positive impact on company value, and capital structure as proxied by the debt to equity ratio did not have a significant impact on company value had a significant negative impact on company value.